PENGGUNAAN MEDIA FLASHCARD DIGITAL UNTUK MENINGKATKAN KEMAMPUAN ANAK DALAM MENGENAL KONSEP BILANGAN DI PAUD CEMERLANG KABUPATEN KAUR PROVINSI BENGKULU - Disrawati Disrawati; Elise Muryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the number recognition capacity among children aged 5 to 6 years through the use of digital flashcard media at Cemerlang Early Childhood Education (PAUD) in Kaur Regency, Bengkulu Province. The investigation used the Classroom Action Research (CAR) methodology as articulated by Kemmis and McTaggart, carried out in two cycles, each consisting of two sessions. Participants in this study consisted of ten children from group B. The data collection methodology included observation, task presentation, documentation, and field notes. The data were subjected to analysis through quantitative and qualitative descriptive techniques. The research findings showed a significant improvement in children's number recognition abilities. In the pre-cycle phase, the learning achievement level was recorded at 40%, which increased to 60% in cycle I, and reached a peak at 90% in cycle II. Improvements were observed in all evaluative indicators, which included identification of numerical symbols, the ability to count numbers sequentially, correspondence of numbers to the appropriate number of objects, and simple number categorization. Thus, it can be concluded that digital flashcard media is effective in improving the ability to recognize numerical concepts in early childhood education.